Oxidized low-density lipoprotein and ankle-brachial pressure index in patients with clinically evident peripheral arterial disease (Clinics, 2010)
OBJECTIVES: To investigate whether oxidized low-density lipoprotein is a suitable predictor of peripheral arterial disease severity. The role of oxidized low-density lipoprotein in the pathogenesis of atherosclerosis has already been investigated. Its relevance as a predictor of the appearance and worsening of coronary arterial disease is also well known. However, the same is not true regarding peripheral arterial disease. METHOD: Eighty-five consecutive patients with an ankle-brachial pressure index (ABPI) < 0.9 and the presence of either intermittent claudication or critical lower leg ischemia were included. The plasma level of IgG autoantibodies against oxidized low-density lipoprotein was evaluated through an enzyme-linked immunosorbent assay. The results were categorized into quartiles according to the ankle-brachial pressure index (a marker of peripheral arterial disease severity), and significant differences were investigated with the Kruskal-Wallis test. RESULTS: There was no significant difference between the quartiles for this population (p = 0.33). No correlation was found between the ankle-brachial pressure index and oxidized low-density lipoprotein levels in subjects with clinically evident peripheral arterial disease with a wide range of clinical manifestations. CONCLUSIONS: Oxidized low-density lipoprotein is not a good predictor of peripheral arterial disease severity.